Calderón-Zygmund estimates for Schrödinger equations revisited - Truong, Le Xuan; Trong, Nguyen Ngoc; Do, Tan Duc (Mathematical Modelling and Analysis, 2025)
We establish a global Calderón-Zygmund estimate for a quasilinear elliptic equation with a potential. If the potential has a reverse Hölder property, then the estimate was known in [6]. In this note, we observe that the estimate remains valid when the potential is merely Lebesgue integrable. Our proof is short and elementary.